Vibrio cholerae Detection by the FilmArray® Gastrointestinal (GI) Panel. (4th October 2017) - Clarke, Kimon; Ton, Han; Bridon, Isabelle; Rogatcheva, Margarita; Demogines, Ann; Henderson, Dave; Saif, Dana; Kanack, Kristen
Abstract: Background: The purpose of this study was to investigate reported false positive FilmArray GI Panel detections of V. cholerae in clinical patient samples. The gold standard for recovery of V. cholerae is routine stool culture. The FilmArray GI Panel contains two sensitive PCR assays for the detection of V. cholerae ; one targets the gyrB gene for genus-level Vibrio identification (focused on detection of V. parahaemolyticus, V. vulnificus, and V. cholerae ) and the second targets the toxR gene for specific identification of V. cholerae . Methods: Clinical samples with discordant V. cholerae detections were requested from source laboratories and then tested on the FilmArray GI Panel. Amplicons from positive samples were extracted, sequenced, and assessed using BLAST search. Results: A total of 14 samples were tested during this study. Three re-tested samples were reported positive for V. cholerae . One sample was confirmed as V. cholerae by the presence of V. cholerae specific gyrB and toxR gene sequences. A second sample was confirmed to be either Vibrio alginolyticus or Vibrio diabolicus by gyrB gene sequence and possessed a 100% homolog to the V. cholerae specific toxR gene. The third sample was confirmed to contain two species of Vibrio: V. cholerae and V. parahaemolyticus . This sample was also confirmed to have the V. cholerae specific toxR gene sequence. The remaining 11 samples resulted in a negative V. cholerae result upon retesting. Conclusion: The investigation confirmed that the FilmArray GI Panel can detect low level V. cholerae organism not recovered by culture. Studies have shown that isolating V. cholerae through specialized media can prove difficult. V. cholerae causing vibriosis can be food-borne or acquired through exposure to affected bodies of water, marine wildlife, or seafood. We found two rare cases, one with the non-cholerae Vibrio species possessing a V. cholerae specific homolog to the toxR regulon and the one novel detection of a co-infection involving two Vibrio species. These data suggest that there will be an increase in Vibrio detections as molecular methods are more sensitive than culture and become much more common for gastrointestinal pathogen testing. Disclosures: K. Clarke, BioFire Diagnostics, LLC: Employee, Salary; M. Rogatcheva, BioFire Diagnostics, LLC: Employee, Salary; A. Demogines, BioFire Diagnostics, LLC: Employee, Salary; D. Henderson, BioFire Diagnostics, LLC: Employee, Salary; D. Saif, BioFire Diagnostics, LLC: Employee, Salary; K. Kanack, BioFire Diagnostics, LLC: Employee, Salary